Study guides

☆☆

Q: How do you factorise xy plus 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

12x2 + 7x + 1 = 12x2 + 3x + 4x + 1 = 3x*(4x + 1) + 1*(4x + 1) = (4x + 1)*(3x + 1)

3x-3x+4x^2+8x=4x^2+8x

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2

=3x+7

Related questions

X=5

x3+xy-x2y2=x(x2+y-xy2)

It is: 3(x+2)

(x + 2)(x + 1)

(x-1)(2x+5)

6y-18+xy-3x its impossible to do anything to it

Factorise it: (x + 5)(3x - 8)

6x^3 + 3x = 3x(2x^2 + 1)

6x^2 + 5x + 1 = (3x +1) (2x + 1)

12x2 - 7x + 1 = 12x2 - 4x - 3x + 1 = 4x(3x - 1) - 1(3x - 1) = (3x - 1)(4x - 1)

if you take a factor of (Y) you end up with Y(X+5Z-2).

(x + 2)(y - 3)

People also asked